Enhancing employability and skills to meet labour market needs in Italy - Garda, Paula (OECD Economics Department Working Papers, 2017)
The various deficiencies of the labour market and the educational system have resulted in high unemployment, low labour force participation, low skills levels and high skill mismatch. Job creation is key to tackling the high unemployment rates, especially for the young and long-term unemployed. Promoting jobs without paying attention to their quality and to the skills required by employers may have adverse impact on welfare and productivity. The Jobs Act and Good School ("Buona Scuola"), two major reforms of the labour market and the educational system, are good steps in the right direction. The Jobs Act and the temporary social security contribution exemptions have contributed to raise employment. By strengthening job search and training policies, the Jobs Act can enhance jobseekers' employability. Increasing the effectiveness of public employment services, given the low spending level, remains a challenge. The Good School reform has the potential to improve school outcomes and provide more aligned skills to the job market. Increasing employability by upgrading skills that match employer needs remains a priority. Business involvement in education and training institutions at all educational levels will be paramount to ensure the provision of relevant skills, the availability of traineeship and apprenticeship places and provide on-the-job training. The adaptability of skills could be encouraged by lowering barriers to labour mobility and boosting work-based learning. This Working Paper relates to the 2017 OECD Economic Survey of Italy (www.oecd.org/eco/surveys/economic-survey-italy.htm)